Retrospective cohort study of adult patients with cystic fibrosis supported with venovenous extracorporeal membrane oxygenation (VV ECMO) at a large German cystic fibrosis center - Achim Grünewaldt; Gernot Rohde (BMC Pulmonary Medicine)
Abstract Background Severe respiratory failure in patients with cystic fibrosis (CF) requiring invasive mechanical ventilation is associated with poor clinical outcomes. The purpose of this study was to evaluate the role of extracorporeal membrane oxygenation (ECMO) in this clinical setting. Methods In this descriptive retrospective monocentric cohort study, we collected data by using electronic medical records from all patients with CF who received ECMO therapy during the period 2012–2021. Setting A monocentric setting at the non-surgical intensive care unit of the University Hospital of Frankfurt, Germany (tertiary care level center and nationally certified CF center). Results During the study period 72 cases of CF patients with intensive care treatment were detected. Of these, 46 cases required mechanical ventilation. Nine patients received ECMO therapy for severe respiratory failure due to pulmonary exacerbation. Eight of the nine patients died in the hospital. This corresponds to an in-hospital mortality rate of 88.9%. None of the patients underwent lung transplantation. The most common CF mutation was the p.Phe508del homo- or heterozygous genotype. Pseudomonas aeruginosa colonization was significantly associated with the in-hospital mortality. Conclusions ECMO support in CF patients and severe hypoxemic failure is associated with high mortality and its use must take into account the increased risk and poor patient outcome in this clinical setting. Clinical trial number This was a retrospective, unregistered analysis. A clinical trial number is not applicable.